Modified Zhujing pill regulates RPE cholesterol metabolism and gut microbiota in an age-related macular degeneration mouse model - Cen, Shuibin; Xie, Shiqin; Ibrahim, Khalid S.; Baran, Michal R.; Li, Xing; Reilly, James; Tan, Zhoujin; He, Zhiming; Shu, Xinhua (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAge-related macular degeneration (AMD) is a common retinal disorder, causing blindness in aged individuals. One of the traditional Chinese medicines, modified Zhujing pill (MZP), has been widely used to treat various ocular disorders, including AMD; however, its protective mechanisms remain elusive. In this study, we explored the functional role of MZP in high-fat-diet-fed mice, a commonly used model for AMD.MethodsCompounds of MZP water extract were identified by high-performance liquid chromatography (HPLC)/mass spectrometry (MS)/MS. The mice were divided into three groups: group 1 mice fed with control diet (CD), group 2 mice fed with high-fat diet (HFD), and group 3 mice fed with HFD for 12 weeks; groups 1 and 2 were then treated with physiological saline, while group 3 was treated with MZP for 4 weeks. The cholesterol level and expression of cholesterol homeostasis-associated genes, antioxidant genes, and proinflammatory cytokines in mouse tissues were measured using biochemical approaches. Mouse cecum microbiota compositions and metabolic functions were analyzed using 16rRNA sequencing and bioinformatics approach.ResultsHFD-fed mice had high levels of cholesterol in the retinal pigment epithelial (RPE) cells, liver, and serum, a decreased expression of cholesterol homeostasis-associated genes and antioxidant genes in the RPE and liver, and an increased expression of proinflammatory cytokines. MZP treatment counteracted HFD-induced pathologic effects. Additionally, HFD altered cecum bacterial compositions and diversities associated with individual metabolic pathways. These metabolic pathways are involved in the biosynthesis of bacterial metabolites, mitochondrial function, oxidative stress, and inflammation. MZP reversed most of the changes back to control characteristics.ConclusionWe postulate that the beneficial effects of MZP against AMD are possibly related to lowering the cholesterol level, suppressing oxidative stress and inflammation, and modulating gut microbiota and associated functions.